PHARMACOETHICS: DEVELOPMENT AND VALIDATION OF INSTRUMENT TO MEASURE KNOWLEDGE, PERCEPTION AND AWARENESS OF GRADUATING PHARMACY STUDENTS ON PHARMACY CODE OF CONDUCT IN MALAYSIA - Zaid, Wan Sazrina Wan; Sulaiman, Mohd Rusyaidi Mohd; Rashid, Shaharuddin Bin Abdul (PEOPLE: International Journal of Social Sciences, 2017)
Pharmacoethics has not been fully explored in Malaysia. This study aimed to create a psychometric instrument based on the Malaysian Code of Conduct for Pharmacists (PCC) for the measurement of its knowledge, perception and awareness among graduating pharmacy students in Selangor and KL, Malaysia, and to test its validity and reliability. Instrument was designed and refined via an expert group discussion and statistical analysis. It contains three sections; personal information, knowledge on PCC and perceptions and awareness on PCC. The instrument was administered randomly to 260 students among 6 institutions that offers undergraduate pharmacy course. Exploratory factor analysis was for validity of the instrument and reliability was measured via Cronbach’s alpha value. Two factors were extracted from 30 items in the knowledge on PCC section and two main factors were extracted from 14 items in perception and awareness on PCC section, classified as General-Knowledge, Practical-Knowledge, Awareness and Perception. After deletion of total of thirteen unstable items, Cronbach’s alpha values were 0.80 (General-Knowledge), 0.63 (Practical-Knowledge), 0.85 (Awareness) and 0.53 (Perception). The scores were: General-Knowledge=53±33(satisfactory), Practical-Knowledge=86±14(good), Awareness=50±19 (moderate) and Perception=46±17(low). These results indicated early evidence of the instrument’s validity and reliability for use in Malaysia and can be used in future studies.